2016
DOI: 10.1007/s13105-016-0491-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CD26/dipeptidyl peptidase IV deficiency on immunophenotypic changes during colitis development and resolution

Abstract: A lot of evidence for the importance of CD26/dipeptidyl peptidase IV (CD26/DPP IV) in immunoactivation has been reported; however, its involvement in colitis remains unclear. The aim of this study was to investigate the influence of CD26/DPP IV deficiency on immunophenotypic changes associated with dextran sulfate sodium (DSS)-induced colitis in wild-type (WT) and CD26-deficient mice. Development of clinical symptoms of colitis and animal health status parameters were assessed; the expression of the nuclear fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…To investigate the influence of DPP-4 in the pathogenesis of DSS-induced colitis, DPP-4-deficient mice were used in DSS treatment, and an increase of myeloperoxidase (MPO) activity and expression of NF-κB p65 subunit in the colonic tissues was observed. Furthermore, an increase in the percentage of splenic CD8 + cells and NKT cells in CD26-deficient mice was observed ( 100 ). In keeping with GLP-2-treated mice, DPP-4-deficient mice also showed a significant increase in macrophages when compared with wild-type mice ( 101 ).…”
Section: Inhibition Of Dpp-4 Function In Ibdmentioning
confidence: 99%
“…To investigate the influence of DPP-4 in the pathogenesis of DSS-induced colitis, DPP-4-deficient mice were used in DSS treatment, and an increase of myeloperoxidase (MPO) activity and expression of NF-κB p65 subunit in the colonic tissues was observed. Furthermore, an increase in the percentage of splenic CD8 + cells and NKT cells in CD26-deficient mice was observed ( 100 ). In keeping with GLP-2-treated mice, DPP-4-deficient mice also showed a significant increase in macrophages when compared with wild-type mice ( 101 ).…”
Section: Inhibition Of Dpp-4 Function In Ibdmentioning
confidence: 99%
“…In DPP-IVdeficient mice induction of colitis by DSS resulted in a stronger increase of myeloperoxidase activity and expression of NF-B p65 subunit in the colonic tissue compared with wildtype mice (Detel et al 2016). Furthermore, in DPP-IV deficient mice, increase in the percentage of splenic CD+ cells and NKT cells as well as increase in macrophages was observed (Detel et al 2016). Salaga et al (2017) demonstrated that EMDB-1, a new peptide analog of endomorphin-2, with a potential to inhibit DPP-IV ameliorated colonic inflammation in both DSS-and TNBS-induced mouse model of colitis.…”
Section: Inhibition Of Dpp-iv As a Potential Therapeutic Strategy In Ibdmentioning
confidence: 94%
“…It has been proposed that the protective effect of DPP-IV inhibition may be a result of increased levels of GLP-1 and GLP-2 (Yazbeck et al 2010b;Ban et al 2011). Detel et al investigated the role of DPP-IV in the pathogenesis of colitis (Detel et al 2016). In DPP-IVdeficient mice induction of colitis by DSS resulted in a stronger increase of myeloperoxidase activity and expression of NF-B p65 subunit in the colonic tissue compared with wildtype mice (Detel et al 2016).…”
Section: Inhibition Of Dpp-iv As a Potential Therapeutic Strategy In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…CD26 is expressed at high level by several T cell subsets including Th17 cells [15] and mucosal-associated invariant T cells (MAIT cells) [16]. Gene knockout mouse studies indicate that CD26 plays both T cell activating [17] and modulatory functions [18].…”
Section: Ucb Derived Foxp3+ T Cells Uniquely Express Cd26 and Cd31mentioning
confidence: 99%